ANALISIS KEBIJAKAN PELAKSANAAN TUGAS KELOMPOK PENYELENGGARA PEMUNGUTAN SUARA (KPPS) - Ceny Agesta; Muhammad Ifra Ahdi Hidayah; Albert Gunawan Wateriri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to discuss the implementation of KPPS duties which is one of the main factors of KPPS officers falling ill and dying. This research uses a qualitative method because it analyzes events in the field to be studied more deeply so as to answer the causes of the death rate of KPPS officers who have passed the health test stage in the KPPS officer recruitment process and have lightened the workload through reducing the maximum DPT limit per TPS. The policy analysis theory used is based on the theory of Applied Policy Analysis by Abdoellah and Rusfiana. The result is the cause of KPPS officers falling ill and dying is the fatigue factor due to the too long voting and vote counting implementation time and the less than optimal management of the division of working hours between KPPS officers. The researcher concluded that there is a need to optimize services by KPPS to voters and the existence of a KPPS Deputy Chairperson.